2017
DOI: 10.5603/kp.a2017.0038
|View full text |Cite
|
Sign up to set email alerts
|

Atrial electromechanical delay analysed by tissue Doppler echocardiography is prolonged in patients with generalised anxiety disorders

Abstract: A b s t r a c tBackground: It has been shown that psychological status is associated with the likelihood of atrial fibrillation (AF). Prolongation of the duration of atrial electromechanical delay (AEMD) is known to be a precursor for AF development.Aim: Therefore, we aimed to evaluate AEMD in patients with anxiety disorder. Methods:In this prospective study, a total of 82 anxiety disorder and 80 healthy subjects were enrolled. Symptoms of anxiety were evaluated by using the Hamilton Anxiety Rating Scale (HAM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A meta-analysis exhibited that AD has made a significant contribution to cardiac events, including an increased risk of cardiovascular mortality, coronary heart disease, and heart failure ( Emdin et al, 2016 ). Patients with AD have been identified to be characterized by prolonged atrial electromechanical delay detected by tissue Doppler echocardiography ( Oksuz et al, 2017 ), which was a herald of AF.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis exhibited that AD has made a significant contribution to cardiac events, including an increased risk of cardiovascular mortality, coronary heart disease, and heart failure ( Emdin et al, 2016 ). Patients with AD have been identified to be characterized by prolonged atrial electromechanical delay detected by tissue Doppler echocardiography ( Oksuz et al, 2017 ), which was a herald of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it might strengthen the data obtained in this valuable study. We thank Russo et al [1] for their interest in our article entitled "Atrial electromechanical delay analysed by tissue Doppler echocardiography is prolonged in patients with generalised anxiety disorders" [2]. In our study, we investigated the atrial electromechanical delay (AEMD) by tissue Doppler imaging (TDI) echocardiography in patients suffering from generalised anxiety disorders, and found that this patient group has prolonged AEMD compared to healthy subjects.…”
mentioning
confidence: 89%